2020
DOI: 10.1155/2020/3926851
|View full text |Cite
|
Sign up to set email alerts
|

Radial Pulse Wave Signals Combined with Ba‐PWV for the Risk Prediction of Hypertension and the Monitoring of Its Accompanying Metabolic Risk Factors

Abstract: Our aim was to study whether radial pulse wave signals can improve the risk prediction of incident hypertension and are associated with its concomitant metabolic risk factors beyond the traditional cardiovascular risk factor Ba-PWV. By enrolling 523 Chinese subjects in this study, linear and stepwise regression analysis was performed to assess the association of radial artery pulse wave signals and Ba-PWV with blood pressure and its related metabolic risk factors such as fasting plasma glucose (FPG), total cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…A single central aortic pulse from another set of experiments (figure 6(c)) exhibits three characteristic waves called systolic wave (P 1 ), tidal wave (P 2 ), and dicrotic wave (P 3 ), in agreement with the literature [36]. The shape and time-domain variables of pulse measured in this work matched with data obtained from a standard DDMX-100 type pulse measurement device [37]; thus, the proposed sensor was accurate as of the standard device (figure S7 and table S1).…”
Section: Wearable Applicationssupporting
confidence: 85%
“…A single central aortic pulse from another set of experiments (figure 6(c)) exhibits three characteristic waves called systolic wave (P 1 ), tidal wave (P 2 ), and dicrotic wave (P 3 ), in agreement with the literature [36]. The shape and time-domain variables of pulse measured in this work matched with data obtained from a standard DDMX-100 type pulse measurement device [37]; thus, the proposed sensor was accurate as of the standard device (figure S7 and table S1).…”
Section: Wearable Applicationssupporting
confidence: 85%
“…Machine learning (ML), the core AI technology, provides intelligent solutions to medical classification problems. Wrist pulse detection technology, including signal identification and processing, has gradually been applied for classification in cardiovascular diseases [11][12][13][14][15]. The development of wearable healthcare devices has facilitated the application of AI to the monitoring of multiple diseases such as CVDs, corneal disease, and cancer [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure pulse wave can be measured at the radial artery, because the radial artery is shallow and its diameter is relatively thick, which is easy to touch and is not easily disturbed by subcutaneous tissue, fat, and other factors. Modern research has indicated that features of the pressure pulse wave in the radial artery can reveal arterial stiffness and indicate cardiovascular function [10,11]. It is recognized that atherosclerosis affects blood vessels throughout the body; coronary atherosclerosis has the same pathological mechanism as large-and medium-sized elastic arteries.…”
Section: Introductionmentioning
confidence: 99%
“…These amplitudes and phases have specific pathophysiological implication reflecting the cardiovascular status. Qi et al [10] incorporated radial pulse wave time-domain feature H3/H1 reflecting peripheral vascular resistance and arterial stiffness into a hypertension risk prediction model and compared it with the model using Ba-PWV. The results revealed that the model using time-domain H3/H1 of pulse signal as a predicting factor had higher accuracy in predicting hypertension risk.…”
Section: Introductionmentioning
confidence: 99%